2016
DOI: 10.3349/ymj.2016.57.1.81
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effect of Renin-Angiotensin-Aldosterone System Blockade in Marfan Syndrome Patients after Aortic Root Replacement

Abstract: PurposeIn this study, we evaluated the long term beneficial effect of Renin-Angiotensin-Aldosterone System (RAAS) blockade therapy in treatment of Marfan aortopathy.Materials and MethodsWe reviewed Marfan syndrome (MFS) patients who underwent aortic root replacement (ARR) between January 1996 and January 2011. All patients were prescribed β-blockers indefinitely. We compared major aortic events including mortality, aortic dissection, and reoperation in patients without RAAS blockade (group 1, n=27) to those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Calcium antagonists have demonstrated improved survival rates in patients with type B dissections [ 88 ]. Both angiotensin‑1 receptor antagonists (losartan) and general blockades of the renin-angiotensin-aldosterone system (RAAS) have been shown to slow aortic dilation [ 235 , 236 ] and the rate of events after surgery [ 237 ] in patients with Marfan syndrome. Accordingly, a beta-blocker should be selected as basic treatment in combination with a calcium antagonist; additionally, a further combination with an angiotensin‑1 receptor antagonist is beneficial for drug-based blood pressure control in the context of rehabilitation for type B dissections.…”
Section: Rehabilitationmentioning
confidence: 99%
“…Calcium antagonists have demonstrated improved survival rates in patients with type B dissections [ 88 ]. Both angiotensin‑1 receptor antagonists (losartan) and general blockades of the renin-angiotensin-aldosterone system (RAAS) have been shown to slow aortic dilation [ 235 , 236 ] and the rate of events after surgery [ 237 ] in patients with Marfan syndrome. Accordingly, a beta-blocker should be selected as basic treatment in combination with a calcium antagonist; additionally, a further combination with an angiotensin‑1 receptor antagonist is beneficial for drug-based blood pressure control in the context of rehabilitation for type B dissections.…”
Section: Rehabilitationmentioning
confidence: 99%
“…The mineralocorticoid receptor antagonists significantly attenuated salt-induced AA. Human studies 11,12 also demonstrated the association between RAAS and AA. In a metaanalysis, 11 ACE I/D polymorphism was a risk factor for AA.…”
mentioning
confidence: 91%
“…In a meta-analysis, 11 ACE I/D polymorphism was a risk factor for AA. Furthermore, Lee et al 12 reported that the addition of RAAS blockade to β-blocker treatment decreased aortic dilatation and clinical events in patients with Marfan syndrome.…”
mentioning
confidence: 99%